PENGEMBANGAN MOBILE LEARNING DENGAN MODEL TAPPS PADA MATERI BARISAN DAN DERET KELAS X SEMESTER I DI SMA NASIMA SEMARANG - Achmad Buchori; Noviana Dini Rahmawati; Sunan Baedowi (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
This study entitled "Development of Mobile Learning Model TAPPS at Content of Sequences and Series Class X Semester 1 at SMA Nasima Semarang". The problems that arise in this research is "How to develop mobile learning with models TAPPS at Content of Sequences andSeriesinSMANasimaSemarang that is valid?, whether assisted mathematics learning with Mobile learning with models Tapps at Content of Sequences and Series in SMA Nasima Semarang is effective?". The population in this study is students of class X first semester of the school year 2014/2015. While the subject of this study was composed of two classes, they are an experiment class and a control class. The number of research subjects for each class is 22 students. Selection and determination of the subjects of this study were taken by purposive sampling technique. This research is Development Research. Developed device is a Mobile learning media with models Tapps at Content of Sequences and series to improve student achievement that meets the criteria of valid and effective. The procedure of this study refers to the development of 4D Thiagarajan but limited to 3 stages: defining, designing and developing. From the results of the researh, it can be concluded that the development of mobile learning with models Tapps at Content of Sequences and Series has achieved an effective indicator, namely: (1) the product of Mobile learning with models Tapps at Content of Sequences and Series gets a validation assessment of media experts 94.2% and material specialists 97.4% with decent criteria. (2) There is a positive response to the mobile learning media demonstrated the effect of 90.3% contribution. (3) Experimental class learning achievement was higher than the control class learning achievement as indicated by the their averages: the average for experimental class is?é?á 94.28 and the average of the control class is 92.59. The results of this study can be used as input for the teacher to try to do the math instructional media development by leveraging technologies such as mobile learning for learning, so that will add insight for teachers and students. Keywords: mobile learning, sequence and series, TAPPS models.